Design of Interactive PowerPoint Media on CTL Model in Primary School - Siti Dewi Maharani; Mazda Leva Okta Safitri; Fatoni Agus Setiawan (Journal for Lesson and Learning Studies)
One of the teacher's tasks is to find ways for students to understand the concept of the lesson without experiencing difficulties. This study aims to produce interactive hyperlink PowerPoint media based on contextual learning models that are feasible to use and to determine their effectiveness. This type of research is Research and Development (R&D) with a 3D+I model (Define, Design, Develop, and Implementation). They collect data in this study using walkthroughs, interviews, and questionnaires. This study involves the assessment of material, media, and design experts. Data analysis techniques using qualitative and quantitative descriptive analysis. The media expert validation assessment results were categorized as "very feasible". The results of the validation assessment from design experts were categorized as "very feasible". The results of the validation assessment from material experts were categorized as "very feasible". In the field trial, the student assessment results were categorized as "very feasible". Based on the results of this study, interactive hyperlink PowerPoint media based on contextual learning models is feasible and effective to use. The results of this study contribute that interactive hyperlink PowerPoint media is feasible and effective to use. The products developed also provide various innovative learning media in the classroom so that students are interested in participating in learning activities.